Fatwas of Sheikh Ali Abdullah Jawan -May Allah have Mercy on him- on Acts of Worship: A Study and Investigation - Jawan, Zainb Hosen; Alwlid, Muhammad Shaaban (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The research is concerned with of the investigation and study of the fatwas of Sheikh Ali Abdullah Jawan on worship with the target of defining of the Mufti and the statement of his approach and rooting of fatwas. The descriptive and analytical approach have been in the theoretical part while documentary approach has been adopted in the investigation of fatwas. One of the most important results reached that the Mufti -may God have mercy on him-committed in his fatwas to the Maliki school، whether the view was well-known or preponderant or what was done by the work and relied in rooting his fatwas mostly on the texts of jurists from their approved books and on some Juristic/textual evidence such as hadith.
Keywords: Ali Jawan; Fatwa; Prayer; Zakat; Fasting